Investigation of sowing date of mother plant effect on germination indices of autumn rapeseed cultivars and lines - Mitra Kheybari; Amir Hossein Shirani rad; Saeid Seyfzadeh; Ismaeil Hahidi; Hamid Reza Zakerin (علوم و فناوری بذر ایران)
This research was done during 2015-2016 as split-plot experiment as RCD with 3 replication in laboratory of Agriculture and Natural Resources Research Center, Zanjan. Sowing date of mother plant as main-plot in 3 levels contained: D1: 7 Oct 2011, 2012 D2: 22 Oct 2011, 2012 D3: 6 Nov 2011, 2012 and 10 cultivars of mother plant included: Opera, Karaj3, KR4, GAo96 × Zarfam (1)(2), Okapi × GAo96 (2)(5), Orient × Modena (2)(4), Orient × Modena (5)(4), Okapi × GAo96 (2)(2), Okapi × GAo96 (5)(2) and GAo96 × Zarfam (5)(1) as sub-plots were considered that conducted in a two year experiments as split-plot as base of RCBD. The studied traits included: germination percent, time required for germination, germination rate, root length, shoot length, seedling dry weight. The result of variance analysis showed that sowing date and cultivar simple effect were significant on mentioned traits. Sowing date and cultivar interaction also was significant effect on mention characteristics. The mean comparison of sowing date and cultivar interaction on germination percent demonstrated that Opera, Okapi x GA096 (5)(2) and GA096 x Zarfam (5)(1) each with mean of 100% had the most germination percent in all sowing date. Generally, results revealed that delaying in sowing date resulted to decreased germination percent. Result showed that cultivars and lines that had the highest germination percent also had the longest root and shoot length.